Impacts of ball-milling on ZSM-5 zeolite properties and its catalytic activity in the two-phase glycerol ketalization with acetone - Lima, Diego S.D. [UNESP]; Zapelini, Iago W. [UNESP]; Silva, Laura L. [UNESP]; Mintova, Svetlana; Martins, Leandro [UNESP] (Elsevier, 2024)
A series of acidic ZSM-5 zeolites were mechanically ball-milled for different periods and further applied as catalysts in the liquid-phase glycerol ketalization with acetone. Structural and textural characterizations showed that the samples had considerable crystallinity and micropore volume loss due to amorphization. On the other hand, due to a comminution effect, the external surface area increased and particle size reduced. TPD and FTIR analyses with probe molecules with different sizes, such as ammonia, pyridine (Py), and 2,6-di-tert-butylpyridine (DTBPy) chemisorbed on the catalyst acid sites, aided in quantifying the various levels of accessibility of chemicals. The treated materials lost acidity due to amorphization or blockage of pores, but the milling enabled higher accessibility of bulkier chemicals to acid sites, as revealed by the chemisorption of Py and DTBPy. A crucial balance of acidity, accessibility, and hydrophobicity was tailored by milling time. The one-hour grounded zeolite had a glycerol conversion 35 % greater than the pristine sample and 67 % greater than the eight-hour milled sample. The results showed that ball milling is a tool to improve the catalytic activity of zeolites with bulky chemicals by fine-tuning the milling time.
Keywords: Accessibility; Chemisorbed pyridines; Mesoporous zeolites; Milling time